Reaction phenomena of catalytic partial oxidation of methane under the impact of carbon dioxide addition and heat recirculation. (15th March 2015) - Chen, Wei-Hsin; Lin, Shih-Cheng
Abstract: The reaction phenomena of CPOM (catalytic partial oxidation of methane) in a Swiss-roll reactor are studied numerically where a rhodium-based catalyst bed is embedded at the center of the reactor. CO2 is added into the feed gas and excess enthalpy recovery is performed to evaluate their influences on CPOM performance. In the study, the mole ratio of O2 to CH4 (O2 /CH4 ratio) is fixed at 0.5 and the mole ratio of CO2 to O2 (CO2 /O2 ratio) is in the range of 0–2. The results reveal that CO2 addition into the influent has a slight effect on methane combustion, but significantly enhances dry reforming and suppresses steam reforming. The reaction extents of steam reforming and dry reforming in CPOM without heat recovery and CO2 addition are in a comparable state. Once CO2 is added into the feed gas, the dry reforming is enhanced, thereby dominating CH4 consumption. Compared to the reactor without excess enthalpy recovery, heat recirculation drastically increases the maximum reaction temperature and CH4 conversion in the catalyst bed; it also intensifies the H2 selectivity, H2 yield, CO2 conversion, and syngas production rate. The predictions indicate that the heat recirculation is able to improve the syngas formation up to 45%. Graphical abstract: Highlights: Catalytic partial oxidation of methane with CO2 addition and heat recovery is studied. CO2 addition has a slight effect on methane combustion. CO2 addition significantly enhances dry reforming and suppresses steam reforming. Dry reforming dominates CH4 consumption when CO2 addition is large. Heat recirculation can improve the syngas formation up to 45%.